Mengungkap Faktor Kesulitan Membaca Bahasa Arab pada Mahasiswa Berlatar Belakang Non Pesantren di PBA UINSU Medan - Sekar Wulandari; Maulida Rahmi; Isnaini Anggina Lubis; Sahkholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The skill of reading is referred to as mahārah qirā’ah in Arabic, which is the third skill after mahārah istima’ and mahārah kalām. In the Arabic Language Education program, some students come from non-boarding school backgrounds and may not have studied Arabic extensively before. This condition can present several challenges, especially in reading Arabic texts. The aim of this study is to analyze the factors that contribute to the difficulty in reading Arabic texts among students from non-boarding school backgrounds in the Arabic Language Education program at UINSU, batch 2021. The method used in this study is qualitative research, with data collection techniques including observation, interviews/questionnaires with five students, and a literature review of previous research. The results of this study show that factors affecting the difficulty in reading Arabic texts among non-boarding school students include their educational background, a lack of understanding of nahwu (syntax) and sharf (morphology), insufficient vocabulary mastery, and a lack of interest in learning Arabic. This study reveals these factors in order to raise awareness among educators about the issue and encourage students to improve their skills in learning Arabic.